Evaluation of rock mass engineering geological properties using statistical analysis and selecting proper tunnel design approach in Qazvin–Rasht railway tunnel - Rahimi, B.; Shahriar, K.; Sharifzadeh, Mostafa (Pergamon, 2014)
Various geological and geotechnical conditions at different project sites require different design, calculation and construction methods. Stability of underground openings depends on ground conditions with different modes of behavior. An essential step in the design procedure is to assess the ground behavior and continuity factor in the tunnel. The objective of this research is to give a methodology for selecting appropriate design approach based on ground behavior and continuity factor in tunnels. The common procedure for determining rock mass properties and in situ stresses are empirical methods, back analysis, field tests and mathematical modeling. In most cases, estimation of rock mass parameters and in situ stresses using empirical methods are not accurate enough. Therefore, rock mass properties are estimated using several empirical equations and statistical analysis were performed to estimation of these properties in order to obtain rational and reasonable results with acceptable accuracy. The Qazvin–Rasht railway tunnel are taken as case study. Behavior types along the tunnel assessed as stable with the potential of discontinuity controlled block failure, several blocks irregular failure, shallow shear failure, plastic behavior (initial), swelling of certain rocks and water inflow.Therefore, appropriate approach for the tunnel support design selected based on classification systems, numerical modelling, observation methods, and engineering judgment. In order to evaluation of tunnel stability, necessary support types and categories RMR, Q, support weight and SRC were employed as empirical tunnel support design methods. The performances of the proposed support systems were analyzed and verified by means of numerical analysis. According to results of empirical and numerical methods and engineering judgment, shotcrete 0.15–0.2 m with wire mesh and light ribs steel sets (IPE160) were proposed as support elements for the tunnel. We found that using proposed approach the optimum support system could be designed.